1991
DOI: 10.1016/s0006-3495(91)82145-2
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ movement in smooth muscle cells studied with one- and two-dimensional diffusion models

Abstract: Although many of the processes involved in the regulation of Ca2+ in smooth muscle have been studied separately, it is still not well known how they are integrated into an overall regulatory system. To examine this question and to study the time course and spatial distribution of Ca2+ in cells after activation, one- and two-dimensional diffusion models of the cell that included the major processes thought to be involved in Ca regulation were developed. The models included terms describing Ca influx, buffering,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 29 publications
3
68
0
Order By: Relevance
“…Model calculations with a calcium buffer value of 300 (Fig. 15) suggest that the gaps between the SR elements (1 sm distance) slow down the spread of calcium ions by more than 1 s or even stop it (Kargacin & Fay, 1991 ' (van Breemen & Saida, 1989). We think that model speculation needs not only data from STOCs and A [Ca2+]c measurements but also from the spatial distribution of Ca2+-transporting and Ca2+-binding molecules.…”
Section: Methodsmentioning
confidence: 98%
“…Model calculations with a calcium buffer value of 300 (Fig. 15) suggest that the gaps between the SR elements (1 sm distance) slow down the spread of calcium ions by more than 1 s or even stop it (Kargacin & Fay, 1991 ' (van Breemen & Saida, 1989). We think that model speculation needs not only data from STOCs and A [Ca2+]c measurements but also from the spatial distribution of Ca2+-transporting and Ca2+-binding molecules.…”
Section: Methodsmentioning
confidence: 98%
“…The two-dimensional model of Ca 2+ diffusion and regulation in smooth muscle cells was described in previous publications (Kargacin, 1994;Kargacin & Fay, 1991;Kargacin & Kargacin, 1997) and will only be described briefly here. The central longitudinal plane of a cylindrical cell segment with a radius of 1mm and of variable length was modeled (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In general, however, the way in which transient Ca 2+ and other second messenger signals interact with effector molecules and regulate cell function has received relatively little attention. In this study, the mathematical models of Ca 2+ diffusion and regulation in smooth muscle cells that were described previously (Kargacin, 1994;Kargacin & Fay, 1991;Kargacin & Kargacin, 1997) were modified and used to study the possible interactions of Ca 2+ with proteins having one or two Ca 2+ -binding sites and different binding kinetics. The characteristics of these interactions and their implications for cell signaling were determined and compared in cellular regions where free diffusion was possible and where diffusion was restricted by the presence of physical barriers to diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have suggested that the plasma membrane pathways (PMCA and Na ϩ -Ca 2ϩ exchanger) account for only 20 to 40% of Ca 2ϩ removal (Cooney et al, 1991), whereas others have concluded that the PMCA removes only ϳ10 to 20% of Ca 2ϩ from the cell (Kargacin and Fay, 1991). However, in a resistance artery from the brain, Kamishima and McCarron (1998) proposed roles only for the Ca-ATPase pumps (SERCA and PMCA), and not the Na ϩ -Ca 2ϩ exchanger, in removal of free Ca 2ϩ from the cytoplasm.…”
Section: B Sarcoplasmic Reticulummentioning
confidence: 99%